2005
DOI: 10.1002/gea.20087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sedimentation and occupation histories inside and outside rock shelters, Keep‐River region, northwestern Australia

Abstract: This paper compares archaeological evidence of Aboriginal occupation inside rock shelters and outside in adjacent sand sheets, focusing on two locations in the Keep-River region, northwestern Australia. Luminescence and radiocarbon dating reveal that occupation sequences inside rock shelters are generally younger (Ͻ 10,000 yr B.P.) than outside (Ͻ 18,000 yr B.P.). Differences in occupation chronology and artifact assemblages inside and outside rock shelters result from depositional and postdepositional process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…7). Unlike Surovell et al (2009), I could not separate closed and open sites for analysis, since these categories are not discrete (many Australian rockshelters have stratified deposits extending beyond the shelter - Smith, 1986;Gould, 1978;Ward et al, 2006) and as dated open sites are otherwise poorly represented in the datasets used.…”
Section: Taphonomic Lossmentioning
confidence: 99%
“…7). Unlike Surovell et al (2009), I could not separate closed and open sites for analysis, since these categories are not discrete (many Australian rockshelters have stratified deposits extending beyond the shelter - Smith, 1986;Gould, 1978;Ward et al, 2006) and as dated open sites are otherwise poorly represented in the datasets used.…”
Section: Taphonomic Lossmentioning
confidence: 99%
“…Specific chronologies have been extrapolated to other sites or broader regions on the basis of stylistic criteria and comparison (e.g. Beaton 1991b;David 1994;Flood and Horsfall 1986;Frost et al 1992;Morwood 1979Morwood , 1986Morwood , 1992bRosenfeld et al 1981;Ward et al 2006). Some shelter art sites have been excavated in order to characterise their lithic assemblages, and it has been assumed that the art and the deposit were contemporaneous phenomena (e.g.…”
Section: The Contemporaneity Of Art and Depositmentioning
confidence: 99%
“…More recent recording work (e.g. Tacon et al 2006) indicates that there are still many engraving sites to be found in the west of the region.…”
mentioning
confidence: 99%
“…This mixed nature of the artifacts and pottery fragments could have been the result of the non-precise, univocal delineation of the stratigraphic horizons in the cave sequence. Alternatively, it could simply represent the outcome of the various taphonomic processes characteristic of cave sedimentary systems, like the syngenetic inwash of surficial sediments into the cave or postgenetic mixing caused by humans or the soil-dwelling fauna [67].…”
Section: Archaeological Interpretations Made In Light Of the New Radimentioning
confidence: 99%